FALSE WITNESS - Slaughter, Karin, 1971- (London : HarperCollinsPublishers, 2021)
Two sisters are faced with a dilemma when one of them has to defend the son of a pedophile they murdered at a young age as a lawyer in a rape case and he says he knows about the murder of his father.
Keywords: Secrecy -- Fiction; Murder -- Fiction; Sex crimes -- Fiction; Sisters -- Fiction; Detective and mystery stories